Longitudinal magnetic resonance findings in delayed posthypoxic leukoencephalopathy. Issue 4 (1st October 2020) - Phan, Mimi N.; Nakawah, Mohammad Obadah
Abstract: Delayed posthypoxic leukoencephalopathy is a rare condition that can occur following prolonged cerebral hypo-oxygenation and manifests as acute onset of neuropsychiatric symptoms after a period of apparent recovery. We describe a case of a 76-year-old man who presented after an unwitnessed fall of unknown duration with initial recovery followed by progressive neurocognitive decline resulting in dementia, dysphasia, and gait apraxia. Initial brain magnetic resonance imaging was unremarkable but repeated brain imaging revealed progressive leukoencephalopathy, which started as small foci of abnormal diffusion restriction in bilateral frontal lobes and gradually evolved over the next 3 weeks to diffuse signal changes in the white matter.